STUDENTS’ MOTIVATION IN COMPLETING ENGLISH ASSIGNMENTS IN ONLINE LEARNING DURING COVID-19 PANDEMIC - Surmiyati; Adelia Nurhidayah; Endang Susilawati (Journey: Journal of English Language and Pedagogy, 2023)
This research aimed to identify students’ levels and the types of motivation that they apply the most to completing their English assignments in online learning at class X in SMAN 1 Sajingan Besar in the academic year 2020-2021. The researcher conducted descriptive research and collected the data using a questionnaire given to 68 students. The first result revealed that students’ motivation for completing their English assignments in online learning was in the middle category at 70.23%. Meanwhile, the second result showed that the type of motivation students applied the most was extrinsic motivation, with 73,68%. The majority of the conditions contributing to students' extrinsic motivation were related to feeling guilty, being aware of the need to improve their English skills, and feeling proud when completing it on time. Then, the students were influenced intrinsically by their feelings of satisfaction and enjoyment. However, amotivation also occurred because of a lack of awareness and a lack of vocabulary mastery. These findings suggest that, even though extrinsic motivation was quite high, students had to have intrinsic motivation and complete their assignments with interest, enjoyment, and satisfaction. The teacher and the parents must support students harder to help them complete assignments in online learning.